Comparative studies of mixed-oxide synthetic routes for the production of ferroelectric PZN-based ceramics - P. Pakawanit (2018)
In this work, comparative studies of three different mixed-oxide synthetic routes i.e. the conventional, the B-site precursor and the combination of B-site precursor and perovskite phase stabilizer on phase formation, microstructure and dielectric properties of ferroelectric lead zinc niobate-based ceramics were demonstrated via a combination of X-ray diffraction, scanning electron microscopy and dielectric measurement techniques. It was found that dense, pure perovskite ceramics with homogenous microstructure and better dielectric properties can be obtained via the B-site precursor technique. © 2013 Copyright Taylor and Francis Group, LLC.